Making Sense Of Mindfulness In Indonesian Elementary Schools: A Phenomenological Exploration Of Pupils’ Lived Experiences Of Concentration And Memory Within The “Merdeka Belajar” Context - Lauw Acep; Dewi Oktaviany (PT. Padang Tekno Corp, 2025)
This study aims to elucidate the essence of Indonesian elementary school students' lived experiences of mindfulness meditation and how it shapes their perceptions of concentration and memory in the context of